The value of events - Lundberg, Erik, 1907-1987; Armbrecht, John, 1981-; Andersson, Tommy D., 1947-; Getz, Donald, 1949- (Routledge advances in event research series, 2017)
The Value of Events fills an important niche in the literature on events, being the first book to comprehensively deal with the subject of value creation and measurement, as opposed to impact assessment and programme evaluation.　 Value creation and measurement is often done routinely from specific perspectives such as tourism, event management, corporate marketing, or customer satisfaction. However, there exist a number of discourses on value and evaluation that have not yet received adequate attention, including the justification of governmental intervention and the costs and benefits of hosting major events. This edited book, written by an international group of academics with expertise in the relevant fields of events, tourism, sport and culture, offers new insight into events and their relationship to sustainability, social responsibility, cultural and social value. Fostering debate in the context of conceptual thinking, philosophising, multiple stakeholder perspectives and interdisciplinary approaches, it challenges the events industry, students, policy-makers and strategists with new perspectives on value, with implications for impact forecasting and assessment.